Controversies in Screening and Diagnostic Criteria for Gestational Diabetes in Early and Late Pregnancy - Huhn, Evelyn A.; Rossi, Simona W.; Hoesli, Irene; Göbl, Christian S. (Frontiers in Endocrinology, 2018)
This review serves to evaluate the screening and diagnostic strategies for gestational diabetes and overt diabetes in pregnancy. We focus on the different early screening and diagnostic approaches in first trimester including fasting plasma glucose, random plasma glucose, oral glucose tolerance test, haemoglobin A1c, risk prediction models and biomarkers. Early screening for gestational diabetes is currently not recommended since the potential benefits and harms of early detection and subsequent treatment need to be further evaluated in randomized controlled trials.